GENDER TRACES in the LIFE STORIES of WOMEN CONVICTS - Küçükbükücü, Ruşen Ayata; Çamur, Gülsüm (Fırat University, 2023)
In this study, gender patterns in the life stories of convicted women are examined. The primary purpose of the research is to reveal the position of convicted women regarding gender in their lives. The Snowball sampling method was used in the research. In-depth interviews were conducted with eight women (those whose conviction process ended and whose conviction process is still ongoing) using a semi-structured interview form. The interviews lasted between 150-210 minutes. In the interviews, women's living spaces were handled as eight separate themes, and interviews were conducted through questions focusing on the content of the themes. Eight themes were determined within the framework of the results obtained. These themes are named as women's personality and psychological characteristics, childhood and family life, education life, working life, social life, marriage life, gender and the effects of gender on different areas of life, women's crime, and sentencing process. The qualitative data obtained were analyzed with the Maxqda 2020 program using the content analysis method and coded. It is seen that the gender roles and gender-specific lifestyles, gender discrimination, and inequalities adopted by the patriarchal society are very effective in the life processes (childhood, education, family relations, social area, marital life, decision to marry, communication with partner, gender roles within marriage, exposure to violence and/or oppression, reasons for committing crimes, etc.) of women.

Bu araştırmada hükümlü kadınların yaşam öykülerinde yer alan toplumsal cinsiyet örüntüleri incelenmektedir. Araştırmanın temel amacı hükümlü kadınların yaşantılarında toplumsal cinsiyetin var olma şekillerini ortaya koymaktır. Araştırmada kartopu örnekleme yöntemi kullanılmıştır. Yarı yapılandırılmış görüşme formu kullanılarak sekiz kadın (hükümlülük süreci biten ve hükümlülük süreci devam eden) ile derinlemesine görüşmeler gerçekleştirilmiştir. Görüşmeler 150-210 dakika aralığında sürmüştür. Elde edilen sonuçlar çerçevesinde sekiz tema belirlenmiştir. Bu temalar; kadınların kişilik ve psikolojik özellikleri, çocukluk ve aile yaşamı, eğitim yaşamı, çalışma yaşamı, sosyal yaşamı, evlilik yaşamı, toplumsal cinsiyet ve toplumsal cinsiyetin farklı yaşam alanlarına etkisi, kadınların suç işleme ve hüküm süreci olarak adlandırılmıştır. Elde edilen nitel veriler içerik analizi yöntemi kullanılarak Maxqda 2020 programı ile incelenmiş ve kodlama yapılmıştır. Kadınların yaşamsal süreçlerinde (çocukluk, eğitim, aile ilişkileri, sosyal alan, evlilik yaşamı, evliliğe karar verme, partner ile iletişim, evlilik içi toplumsal cinsiyet rolleri, şiddete ve/ya baskıya maruz kalma, suç işleme nedenleri vb.) ataerkil toplumun benimsediği cinsiyet rolleri ve cinsiyetlere özgü yaşam biçimlerinin, cinsiyet ayrımcılığının ve eşitsizliklerin oldukça etkili olduğu görülmektedir.
KADIN HÜKÜMLÜLERİN YAŞAM ÖYKÜLERİNDE TOPLUMSAL CİNSİYET İZLERİ
Keywords: Social and Humanities Education (Excluding Economics; Business and Management); Sosyal ve Beşeri Bilimler Eğitimi (Ekonomi; İşletme ve Yönetim Hariç)